Improving the Quality of Bio-Oil Produced from Rice Husk Pyrolysis by Extraction of its Phenolic Compounds - Fardhyanti, Dewi Selvia; Chafidz, Achmad; Triwibowo, Bayu; Prasetiawan, Haniif; Cahyani, Novia Noor; Andriyani, Sinta (Jurnal Bahan Alam Terbarukan, 2019)
Rice husk is an agricultural waste which contains 50% cellulose, 25%-30% lignin and 15%-20% silica. It can be used as raw material of bio-oil. Bio-oil is liquid which produced by pyrolysis process. Bio-oil can be produced from the rice husk at 773 and 873 K. The main component of Bio-oil from rice husk pyrolysis at 773 and 873 K is phenolic compounds about 47.98% and 62.65%, respectively. It causes corrosive, low heating value, high acidity, high viscosity and unstable that causing an engine damage. The presence of phenolic compound decreases the quality of bio-oil. Therefore, it needs a process such as liquid-liquid extraction to reduce the phenolic compound using 80% methanol and 80% chloroform as a solvent. The extract and raffinate phase were analyzed using UV-Vis spectrophotometer. The aim of this research determine the effect of temperature pyrolysis for the characterization of bio-oil, the stirring speed and the temperature of the extraction for the distribution coefficient and the yield of phenolic compound. The results showed that the characterization of bio-oil produced from rice husk pyrolysis at 773 and 873 K are densities 1,040 and 1,042 Kg/m3; viscosities 9.3488 and 9.5007 cSt; acid numbers 46.75 and 52.45 mg KOH/g; pH 2.5 and 3; flash points 426 and 423 K and heating values 3.229 and 3.339 MJ/kg, respectively. The highest distribution coefficient and yield were obtained at 323 K and a stirring speed of 250 rpm. The distribution coefficient of bio-oil produced by pyrolysis at 773 and 873 K is 1.504, and 1.528, respectively. The yields of bio-oil produced by pyrolysis at 773 and 873 K are 58.885%, and 48.429%, respectively.Ã‚Â Ã‚Â